Development and Application of a Rasch Model Measure of Student Competency in University Introductory Computer Programming - Waheed, Leela (Curtin University, 2018)
University computer programming instruction nomenclature commonly uses the term Computer Science 1 (CS1) to describe introductory units of study. Success in CS1 is important as a pre-requisite for further study in programming and related disciplines. It is important to measure student progress and the antecedent influences. This study applied the Rasch Model and Messick’s Unified Theory of Validity to construct an interval level measure of CS1 competency with demonstrable suitability for this purpose.